A fast and robust method to clone and functionally validate T-cell receptors - Birkholz, Katrin; Hofmann, Christian; Hoyer, Stefanie; Schulz, Bastian; Harrer, Thomas; Kämpgen, Eckhart; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (Journal of Immunological Methods, 2009)
Sequencing, cloning and functional testing of T-cell-receptor (TCR) α- and β-chains from T-cell clones is often required in immunotherapy and in immunological research. However, the determination of the TCR chains by a simple PCR is not possible, since, in contrast to the 3′ constant domain and untranslated region (UTR), no conserved sequences are present in the 5′ region. Furthermore, subsequent functional testing of cloned TCRs requires laborious cell-culture experiments, often involving primary human material and time-consuming viral transduction strategies. Here we present a universal PCR-based protocol, adapted from the capswitch technology, that allows for amplification of the TCR α- and β-chain mRNAs without knowledge of the TCR variable domain subtype by attaching a designed sequence to the mRNA's 5′ end. Two different MelanA/HLA-A2-specific and one HIVgag/HLA-A2-specific TCR were cloned that way, and were functionally tested by a newly developed easy, fast, and low-cost method: we electroporated Jurkat T cells simultaneously with TCR-encoding RNA and an NFAT-reporter construct, and measured the activation status of the cells upon specific stimulation. The results of this assay correlated with the cytokine release, functional avidity, proliferative activity, and the ability to recognize MelanA/HLA-A2-presenting tumor cells of bulk T cells electroporated with RNA encoding the same TCR. Together these two protocols represent a rapid and low-cost tool for the identification and functional testing of TCRs of T-cell clones, which can then be applied in immunotherapy or immunological research. © 2009 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Cellular immunology; Immunotherapy; Signal transduction; T cells; TCR